Mengoptimalkan Peran Ulama dalam Mempromosikan Toleransi Beragama di Aceh - Muslem Muslem (Institut Nalanda, 2023)
Religious intolerance is a growing problem in Aceh, Indonesia. Ulama as a religious leader, has an important responsibility in addressing the phenomena of intolerance and building religious tolerance in society. This article discusses the phenomenon of interreligious intolerance in Aceh and the responsibility of believers in promoting religious tolerance. Based on the literature study, the author presents a survey of the history and factors that influence religious intolerance in Aceh and scholars as agents of change in addressing the problem. In addition, this article also reviews strategies that scholars can do in promoting religious tolerance in Aceh, such as through dakwah, religious education, inter-religious dialogue, and real actions that reflect the values of tolerance. This paper hopes to contribute to strengthening efforts to build religious tolerance in Aceh and Indonesia.